Constitutional supremacy & international human rights: An appraisal - Noor Ashikin, Hamid; Nazli, Ismail@Nawang; Nuramani, Pauzai; Noraida, Harun (2016)
International law cannot override the supreme constitution of sovereign states. Section 4(4) of the Human Rights Commission of Malaysia Act 1999 allows regard to be had to the Universal Declaration of Human Rights (UDHR) 1948 as long as it is not inconsistent with the Federal Constitution. Section 4 (4) mentions: ―For the purpose of this Act, regard shall be had to the Universal Declaration of Human Rights 1948 to the extent that it is not inconsistent with the Federal Constitution.‖ In case of conflict between international norms and national rules, courts must adopt the rule that national law prevails. However there is no clear practice adopts by the judges in using internationals norms while making the decision. The objective of this paper is to examine the application of international human rights in the context of Malaysian existing cases alleging of violation of human rights. The study is qualitative in nature. Data are collected from legal cases and treaties as primary sources. The analysis is done in descriptive and analytical manner. It was found that the decisions of the courts which taking into consideration of human norms able to promote the object of the constitutional guarantee in Malaysia.